(untitled) (Semiárida, 2020)
During botanical explorations carried out in Malargüe, between 2003 and 2005, 940 specimens were collected, and 39 taxa are recorded for the first time for Mendoza province, Argentina. Characteristics of habitat and life form are given for each taxon. Common names of some of these taxa are given, based on the oral information obtained from the local people.